Impact of Excessive Nitrogen Fertilization on the Biochemical Quality, Phenolic Compounds, and Antioxidant Power of Sesamum indicum L Seeds. (4th March 2019) - Elhanafi, Laila; Houhou, Mariame; Rais, Chaimae; Mansouri, Ismail; Elghadraoui, Lahsen; Greche, Hassane
Abstract : Nitrogen is an essential nutrient for plants life cycle. However, the excessive use of this element causes serious problems in agriculture. This can disrupt the development of many important plants. Sesamum indicum or sesame represents one of the most economically important and ancient oil crops in the world. In fact, its seeds are used for many biological activities. The aim of the present study is to evaluate the effect of high levels of nitrogen on some primary and secondary metabolites and the antioxidant activity under different levels of N supply. Results analysis of our investigation showed that the excessive nitrogen supply had a serious effect on the quality of sesame seeds. In fact, N fertilizer promoted the accumulation of proteins until 57.16%, in detriment of oil and sugars that decreased with 49.43% and 16.27%, respectively. Also, total phenolic, flavonoids content, and antioxidant activity showed a significant decrease.